2021
DOI: 10.18632/aging.202824
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA C2dat2 facilitates autophagy and apoptosis via the miR-30d-5p/DDIT4/mTOR axis in cerebral ischemia-reperfusion injury

Abstract: Cerebral ischemia-reperfusion injury (CIRI) is an important pathophysiological process of ischemic stroke associated with various physiological and pathological processes, including autophagy and apoptosis. In this study, we examined the role and mechanism of long noncoding RNA CAMK2D-associated transcript 2 (C2dat2) in regulating CIRI in vivo and in vitro . C2dat2 up-regulation facilitated neuronal autophagy and apoptosis induced by CIRI. Mechanistically, C2dat2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…One possible explanation could be that since knockdown of the Lnc-PVT1 could moderate the loss of neuron [4], we assumed deteriorative AIS patients' RFS might result from Lnc-PVT1 overexpression. Another explanation could be that in AIS patients, the overexpression of Lnc-PVT1 might cause a poor prognosis through interacting with the notorious adverse prognostic factors, such as ischemia/reperfusion injury [16,17]. However, the current hypothesis needed to be further verified, since related reports remained scarce.…”
Section: Discussionmentioning
confidence: 94%
“…One possible explanation could be that since knockdown of the Lnc-PVT1 could moderate the loss of neuron [4], we assumed deteriorative AIS patients' RFS might result from Lnc-PVT1 overexpression. Another explanation could be that in AIS patients, the overexpression of Lnc-PVT1 might cause a poor prognosis through interacting with the notorious adverse prognostic factors, such as ischemia/reperfusion injury [16,17]. However, the current hypothesis needed to be further verified, since related reports remained scarce.…”
Section: Discussionmentioning
confidence: 94%
“…miR-30d-5p targeted the 3′-UTR site of Beclin1 mRNA and participated in autophagy in a newborn rat HI brain via regulating Beclin1. The C2dat2/ miR-30d-5p/DDIT4/mTOR axis formed a new signaling pathway facilitating autophagy induced by cerebral ischemia reperfusion injury (Xu et al, 2021). Specifically, C2dat2 blocked the targeting function of miR-30d-5p on DDIT4, and promoted the upregulation of DDIT4 and Beclin-1 levels.…”
Section: Cell Autophagy and Apoptosismentioning
confidence: 98%
“…AntagomiRs of miR-30d promoted autophagy and reduced apoptosis in post-ischemia astrocytes [ 150 ] and neonatal rat neurons [ 151 ], while another study demonstrated that miR-30d decreased neuroinflammation by reducing autophagy in macrophages and subsequently promoting M2 macrophage polarization over M1 [ 152 ]. Additionally, the sponging of miR-30b and miR-30d by lncRNAs SNHG12 (small nucleolar RNA host gene 12) and C2dat2 (CAMK2D-associated transcript 2), respectively, was shown to increase autophagy and apoptosis after cerebral ischemia–reperfusion injury [ 146 , 153 ].…”
Section: Specific Mirnas In Modulation Of Autophagy In Preclinical Mo...mentioning
confidence: 99%